2022
DOI: 10.1371/journal.pone.0275631
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical amplitude modulation structures and rhythm patterns: Comparing Western musical genres, song, and nature sounds to Babytalk

Abstract: Statistical learning of physical stimulus characteristics is important for the development of cognitive systems like language and music. Rhythm patterns are a core component of both systems, and rhythm is key to language acquisition by infants. Accordingly, the physical stimulus characteristics that yield speech rhythm in “Babytalk” may also describe the hierarchical rhythmic relationships that characterize human music and song. Computational modelling of the amplitude envelope of “Babytalk” (infant-directed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…half notes), while the lower hierarchy corresponds to a frequency band (approximately, 3 Hz <) of syllable and musical notes (e.g. quarter notes) 19 . Such a hierarchical structure of rhythm can be visualized from the AM envelope of sound waveforms 20 , 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…half notes), while the lower hierarchy corresponds to a frequency band (approximately, 3 Hz <) of syllable and musical notes (e.g. quarter notes) 19 . Such a hierarchical structure of rhythm can be visualized from the AM envelope of sound waveforms 20 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…quarter notes) around 4–12 Hz while the higher hierarchy corresponds to prosody, intonation, and long musical notes (e.g. half notes) around 1–3 Hz 19 . There are also rhythms around 12–30 Hz that correspond to phonemes or sound onsets at even lower levels of the hierarchy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of modulations in amplitude has been investigated, especially with an interest in the neural responses to the speech/musical signal. The spectrum of speech modulation (for a small set of language corpora) ranges between 4 and 5 Hz, while the spectrum of music modulation (for a small set of musical genres) ranges from 1 to 2 Hz (Daikoku & Goswami, 2022; Ding, Patel, et al., 2017). The similarities in metrical organisation and the assumption that critical information is conveyed in specific time frequencies (Pellegrino et al., 2011) have increasingly motivated the investigation of the relationship between metre perception and attention.…”
Section: Domain‐general Approachesmentioning
confidence: 99%
“…Such phonological hierarchy can be identified from the amplitude modulation (AM) hierarchy of speech waveforms below approximately 40 Hz. Evidence has shown that AM hierarchy of speech signals, including prosody, syllable, and phoneme, can be detected in the temporal structure of speech waveforms such as delta (<4 Hz), theta/alpha (4-12 Hz), and beta/ low gamma , respectively, regardless of speech types [13,18]. Linguistically, such phonological hierarchy is classically represented as a tree that captures the relative prominence of units [16,19] (Fig 1).…”
Section: Phonological Hierarchy In Speech Rhythmmentioning
confidence: 99%